Investigating Teachers' Perceptions of Their Own Teaching Effectiveness during Covid‑19 pandemic in the online EFL Courses - Navidmoghaddam, Alireza (Indonesian TESOL Journal, 2023)
This study examined teacher perspectives of EFL online instruction in a Turkish higher education institution during COVID-19. Due of the global COVID-19 pandemic, many university teachers who used face-to-face teaching had to change their approaches. A revised electronic Technological Pedagogical Content Knowledge (TPACK) survey was used to analyze participants' perceptions on their own online teaching at COVID19. It also looked at the issues EFL teachers faced during the COVID-19 pandemic and their ideas for a more successful online EFL teaching experience. Thirty-six only female instructors took part in the study by filling out an online questionnaire. Overall, the data supports a favorable impression of online education's efficacy. Participants in this study felt that the online experience allowed them to develop as learners. It was also discovered that students' interest in studying increased when they took classes online. Training for teachers, technical assistance, enabling Blackboard's extra features, and flexibility with exams and class configuration were recommended for a more productive online experience.